The status of science education research - Hernandez, Dolores F.
Two things stand out significantly as one thinks about bridging the gap between advances of modern science and the teaching of science in schools and colleges. One is that the content of school science needs to be brought up to date so that it includes new ideas and developments of modern science. The second point is that the practices of teaching need to be influenced more by results of investigations and research studies that has been the case up to the present.
Keywords: Science -- Study and teaching -- Research -- Philippines; Science -- Study and teaching -- Research -- United States